Rekonstruksi Pendidikan Agama Islam Berbasis Kearifan Lokal dalam Penguatan Karakter dan Moderasi Beragama di Era Disrupsi - Baiq Mulianah; Budi Hardjono; Junaidi Junaidi; Ahmad Munir Ardiansyah (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2026)
The era of digital disruption has brought significant changes to the practice of Islamic Religious Education (IRE), leading to a shift in educational orientation from character formation toward the dominance of normative knowledge transmission. This condition has generated serious challenges, including the weakening of value internalisation, a crisis of character, and declining sensitivity to local cultural contexts within religious education. This article aims to formulate a model for reconstructing Islamic Religious Education based on local wisdom to strengthen character development and religious moderation in the era of disruption. The study employs a qualitative approach with an ethnographic design, utilising observation, in-depth interviews, and documentation, and is analysed thematically and interpretively within a socio-cultural framework. The findings indicate that local wisdom plays a strategic role as both an epistemic medium and a form of social praxis in the internalisation of Islamic values that are contextual, inclusive, and sustainable. The reconstruction of Islamic Religious Education based on local wisdom enables the integration of cultural values, the formation of moderate character, the strengthening of economic self-reliance, and the use of arts and local traditions as media for value-based education. This article proposes a conceptual model of Islamic Religious Education reconstruction grounded in four integrative pillars: Islamic Religious Education as the transmission of cultural values, the strengthening of character and religious moderation, economic literacy and self-reliance, and adaptability to digital disruption. This model affirms that Islamic Religious Education must be developed holistically and contextually in order to remain relevant as value-based education that responds to contemporary change without losing its cultural roots and Islamic values.